2006
DOI: 10.1063/1.2140277
|View full text |Cite
|
Sign up to set email alerts
|

High-pressure x-ray diffraction and Raman spectroscopy of ice VIII

Abstract: In situ high-pressure/low-temperature synchrotron x-ray diffraction and optical Raman spectroscopy were used to examine the structural properties, equation of state, and vibrational dynamics of ice VIII. The x-ray measurements show that the pressure-volume relations remain smooth up to 23 GPa at 80 K. Although there is no evidence for structural changes to at least 14 GPa, the unit-cell axial ratio c∕a undergoes changes at 10–14 GPa. Raman measurements carried out at 80 K show that the νTzA1g+νTx,yEg lattice m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

13
69
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(82 citation statements)
references
References 40 publications
13
69
0
Order By: Relevance
“…Differences between the phonon density of states of ice VIII obtained at the PBE and vdW-DF2 level of theory are instead minor. Recent Raman measurements of the stretching vibrations [15] indicate that the frequencies are approximately 3350, 3440, and 3470 cm À1 , consistent with our calculations. The bending modes show little change with respect to either phase or functional, and the rotational and translation modes are redshifted when using vdW-DF2, with respect to PBE results.…”
supporting
confidence: 90%
See 2 more Smart Citations
“…Differences between the phonon density of states of ice VIII obtained at the PBE and vdW-DF2 level of theory are instead minor. Recent Raman measurements of the stretching vibrations [15] indicate that the frequencies are approximately 3350, 3440, and 3470 cm À1 , consistent with our calculations. The bending modes show little change with respect to either phase or functional, and the rotational and translation modes are redshifted when using vdW-DF2, with respect to PBE results.…”
supporting
confidence: 90%
“…[17] by using PBE. The inclusion of the ZPE worsens the agreement with experiment [15], primarily because of the volume overestimate [28]. We note the much better agreement with experiment obtained for the binding energy of ice VIII when using the vdW functional.…”
Section: -2mentioning
confidence: 61%
See 1 more Smart Citation
“…This clearly shows competing quantum effects: hydrogen bonding decreases the ZPE associated with stretch and increases that of the bend vibrations. This is also seen in high pressure experiments on ice VIII: with increasing pressure the frequency of the stretch modes decreases and those of the librational modes increase (164,165). In addition, as shown in …”
Section: Isotope Fractionation As a Probe Of Nuclear Quantum Effectssupporting
confidence: 63%
“…X-ray scattering spectra consequently can allow for clear determination of phase boundaries, and provide very clear ways to compare theory and experiment. A number of x-ray studies of ice VII [8][9][10], ice VIII [11] and ice X [12] exist. It has also been suggested that ice VII might exist in cold conducting slabs within the Earth's mantle [13].…”
mentioning
confidence: 99%